PESAN MORAL DALAM CERITA RAKYAT TOMBULU MA’PALUS (SUATU KAJIAN SEMANTIK) - Jenie Posumah (KOMPETENSI, 2022)
One of folktales is a fable. Fable is a traditional short story, especially with animals, as the characters, that teaches a moral value or moral lesson. In Minahasa, a part of tribe in North Sulawesi Province, also has a fable , entitled ‘Ma’palus’ or in another title some of Minahasan people said ‘Ma’sawasawangan Takaz I Mate’. This story told the good things that shown by some animals as the main characters. The characters of this story were a shrimp ‘sapun’, an ant or a small red ant (another word fire ant) ‘lalam∂ntik’, and a snail ‘ kolombi’. Wherever they went, whatever they did, they were always together even in any situation. The aimed of this study was to show the good, the positive things must be done by the human beings based on the role of the characters’ attitudes performed in this story. ‘Ma’sawasawangan Takaz I Mate’ or ‘Ma’palus’ (help one another) solidarity, work hard, diligent, are some of the good things that human beings should do in their daily life.This research was a qualitative research with descriptive method used to describe into narrative form while using participant observation technique by literary study and the writer was as the primary instrument.The result of this research was could be used as a good way to form the good behavior, attitude and characters of the people especially in Tomohon City. Also, this research could be used as a good tool to converse the National culture (generally) and local culture (specifally).